Islamic Civilization's Contributions to Modern Governance - Sanusi Lafiagi Haruna (Universitas Pendidikan Ganesha, 2024)
Islamic civilization has left an indelible mark on the world, with its influence extending to various aspects of modern governance. From administrative innovations to philosophical contributions, Islamic civilization has shaped political thought and practice globally. This study aims to analyze the historical influence of Islamic civilization on governance, highlighting its philosophical, legal, and administrative contributions. As well as, examine the contemporary relevance of these influences and their impact on political systems and societal dynamics. This research is a qualitative study using the literature review method. Data collection was obtained by studying the literature using documents and articles to obtain information about the subject, namely about the contribution of Islamic Civilization to Modern Government. Data analysis was carried out using data interpretation techniques and providing sufficient theoretical explanations related to the problem at hand. The results show that Islamic Civilization has had a profound and lasting impact on modern governance. From administrative innovations in Islamic kingdoms to the influence of Islamic legal and philosophical thought, Islamic civilization has shaped political systems and social organizations globally. By acknowledging and studying these contributions, we gain valuable insight into the richness and complexity of Islamic civilization and its enduring legacy in shaping the world we govern today.